Gace Brulé and his rivals in the art of singing and love: performing a song at a concert - Ludmilla Evdokimova (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. 3, Filologii͡a, 2024)
In the lyrical songs of Gace Brulé, one of the first French trouvères (probably born c. 1159 and died after 1213), a performance art orientation is obvious: his songs in many cases allow us to recreate the conditions of their performance; it follows from them that the poet addressed not only the lady, but also a gathering of listeners, among whom were his patrons and other poets, and Gace more than once emphasized his rivalry with his brothers, challenging them to competition; such songs account for more than two-thirds of those attributed to him in H. Petersen Dyggve's edition. The theatrical expressiveness of Gace's poetry is due to the fact that in his collection of poems, as well as in other's poets of the late 12th and even later times, the lyrical song and jeu-parti, formed, like the Provençal tenson, by the dialogue of interlocutors, are not completely differentiated: his collection poems includes only one jeu-parti, consisting entirely of dialogue — perhaps the earliest example of this genre in the poetry of the trouvères — while elements of argument with other poets are integrated into the songs. A comparison of Gace's songs with the songs of his contemporaries and younger contemporaries (Blondel de Nesle, Châtelain de Coucy, Thibaut de Champagne, Richard de Fournival) shows that his orientation towards performance art is much more pronounced than that of other trouvères of his time. Gace is superior in this regard to those troubadours whose songs also contain appeals to patrons or other poets presumably present among the listeners — like Guillaume IX d'Aquitaine' songs to «friends» (n 1-3) or some of Bernard de Ventadorn' songs addressed to «seigneur» (gentlemen); however, such songs constitute a significantly smaller part of their heritage compared to Gace. The theatrical expressiveness of Gace’s songs is created, in addition to numerous addresses to listeners or other poets, by the dialogues of imaginary interlocutors included in them. We can conclude that the characteristic features of Gace’s poems correlate not only with the history of small genres — jeux-partis and songs, the contours of which had not yet developed in the poetry of the trouvères of his time, but also with the peculiarity of his talent.